URGENCY OF COMMUNITY INVOLVEMENT IN THE FORMATION OF REGULATIONS TO CREATE RESPONSIVE POLICIES - Aimi Solidei Manalu; Fitriani Ahlan Sjarif (Universitas Muhammadiyah Ponorogo, 2023)
Law 12/2011 to be revised a second time to become Law 13/2022 and followed by the issuance of Government Regulation (PERPPU) 2 of 2022 on Job Creation. This study employed normative legal research methods that focused on regulating community involvement in the Indonesian legal system and the urgency of community involvement. The importance of community involvement at every stage of the formation of regulations are able to produce responsive and acceptable rules for the community, create collective intelligence, and build inclusive and representative legislatures. The concrete solution aims to provide digital applications to accommodate people's aspirations.